Анатомо-функциональный очерк плечевого сплетения каспийской нерпы (Pusa caspica) - Василевская, Г.И.; Веселовский М.В. (Вестник зоологии, 1999)
В грудной конечности (ГК) этого вида, которая выполняет вспомогательные локомоторные функции, представлены все звенья ГК наземных млекопитающих. В скелете — четкие признаки вторичных модификаций, большинство мышц хорошо развиты. Уровни выхода нервов плечевого сплетения (ПС) совпадают с таковыми в ряду представителей наземных хищных, — С1У-ТМ-П. В общем схема компоновки ПС отражает один из вариантов иннервации конечности с ограниченным набором двигательных актов. In this seals species all the parts of terrestrial fore leg are presented in this species of seal. Brachial plexus (BP) nerves leave the spinal cord at levels of CIV-Thl-Il, thus their departure coincides with that of predator mammals. There is a typical set of separated nerves for the belt and free extremity, although they are shortened. The skeleton has clearly signs of secondary modifications, most muscles are well developed. In common, the composition pattern of BP reflects one of rtructural variances for innervation of leg capable to perform a limited range of motor acts.